PENGGUNAAN APLIKASI CANVA DALAM PEMBUATAN POSTERPADA PEMBELAJARAN SENI BUDAYA UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWA KELAS VIII.H SMP NEGERI 8 DENPASARTAHUN PELAJARAN 2022/2023 - Ni Putu Elma Rahayu; I Made Sujana (SOSPENDIS : Sosiologi Pendidikan dan Pendidikan IPS, 2023)
This study aims to determine the learning activity of class VIIIH students of SMP Negeri 8 Denpasar in making posters in learning arts and culture. This research method uses Classroom Action Research which is carried out in two cycles with each cycle consisting of planning, implementation, action, observation and reflection. The subjects of this study were VIIIH class students with a total of 40 students. The results of this study are increasing to increase the learning activity of Class VIII students. H SMP Negeri 8 Denpasar 2022/2023 Academic Year. This is evidenced by an increase in student learning activity in cycle I and cycle II which has increased. In Cycle I the number of students who completed 14 students (35%) with an average score of student learning outcomes reached 1.84. 35% have not met the set classical completeness, which is 75% of the total number of students. Whereas in cycle II the number of students who passed experienced an increase of 32 students (80%) with an average student score of 2.27. Based on the results of this study, it can be concluded that using the Canva application in making posters in arts and culture lessons can increase the learning activity of making posters for class VIIIH students of SMP Negeri 8 Denpasar in the 2022/2023 academic year.